G-protein coupled receptors synergy in bone health: new avenues for osteoporosis detection and in vitro modeling - Sopova, Julia V.; Krasnova, Olga A.; Kriukova, Julia D.; Mukhamedshina, Yana O.; Zakirova, Elena Y.; Rizvanov, Albert A.; Lesnyak, Olga M.; Neganova, Irina E. (Frontiers in Endocrinology, 2025)
Osteoporosis remains a substantial healthcare burden in modern times. Current diagnostic methods of osteoporosis detect changes in bone mineral density and microarchitecture, which have already occurred. It is critically important to develop methods of early diagnosis of osteoporosis to be able to plan early interventions in order to stop the disease progression. Genetic screening based on early osteoporosis marker genes appears to be a promising approach for early diagnosis and prevention. However, a significant gap exists in this area of knowledge. Recently, we identified a novel combination of three single nucleotide polymorphisms – FSHR (rs6166) AA, TSHR (rs1991517) CC, and ADRB2 (rs1042713) AA, with a high prevalence among osteoporotic patients. Subsequent functional studies using patient-derived mesenchymal stem cell lines revealed impaired osteogenic differentiation capacity. To clarify the role of these polymorphism combinations, this review first examines the physiological aspects of each receptor and the identified single nucleotide polymorphisms at the organismal level. It then analyzes their contribution to the dysregulation of bone remodeling, with a particular focus on osteoblastogenesis. Understanding these mechanisms opens up new opportunities for the development of early osteoporosis diagnosis and stratification of personalized treatments for patients.